Analisis Hukum Terhadap Urgensi Pendaftaran Merek Bagi Pelaku Usaha Mikro, Kecil, Dan Menengah (UMKM) (STUDI PUTUSAN NOMOR 646 K/Pst.Sus-HKI/2021) - T Fairuz Jasmine (Iuris Studia: Jurnal Kajian Hukum, 2021)
Trademark registration is an important thing that must be done in business, especially micro, small and medium enterprises (MSMEs). One of the reasons is because trademark registration provides legal protection for business actors so that their trademarks are not used by other parties, so that they can anticipate the occurrence of trademark disputes in the future. The urgency of trademark registration for MSME actors is due to the many cases of trademark dispute lawsuits that occur in MSME actors. One example is the case of the “Bodyguard” brand lawsuit. Problems: 1) How is the application of the principle of good faith related to the element of brand passing-off? 2) What is the urgency of trademark registration for Micro, Small and Medium Enterprises (MSMEs)? 3) What are the legal considerations for the judge in the decision regarding the "Bodyguard" brand dispute number 646 K/Pst.Sus-HKI/2021 involving Micro, Small and Medium Enterprises (MSMEs)? The research method is normative juridical, which is descriptive analytical with data collection techniques from library research. Data analysis was carried out using a qualitative normative method, where this research was classified as normative which was complemented by a comparison of secondary data research. The results of the study, namely the urgency of trademark registration for Micro, Small and Medium Enterprises (MSMEs) are still very low due to lack of awareness of the impact of losses that may occur. Legal protection for trademarks from passing off acts in the Indonesian legal constitution has not been specifically regulated in the trademark laws and regulations in Indonesia, but there are several articles that imply their inclusion in Law no. 20 of 2016. Legal considerations for judges in the decision regarding the dispute over the "Bodyguard" brand number 646 K/Pst.Sus-HKI/2021 involving Micro, Small and Medium Enterprises (MSMEs), in legal considerations in favor of the defendant/cassation petitioner in the dispute case The "Bodyguard" brand is correct and in accordance with the legal system in force in Indonesia, which adheres to a constitutive system (first to file), where trademark rights are obtained through registration